The Characteristics and New Treatment Paradigm of Dental Implant–related Chronic Rhinosinusitis. Issue 3 (May 2013) - Chen, Yi-Wei; Huang, Chi-Che; Chang, Po-Hung; Chen, Chiang-Wen; Wu, Chia-Chen; Fu, Chia-Hsiang; Lee, Ta-Jen
Background: Because dental implantation and sinus augmentation are widely performed in recent years, one of their possible complications, maxillary sinusitis, has become a major concern for both dentists and otolaryngologists. This study evaluates the characteristics of dental implant–related chronic rhinosinusitis (DIrCRS) and the outcome of endoscopic sinus surgery (ESS) for these patients. Methods: Eighteen patients diagnosed with DIrCRS from 2007 to 2012 and who were recommended for operation were included. ESS served as the first surgical choice. Dental implants were not routinely removed unless there was severe periimplantitis. All data, including CT and surgical findings, were collected and analyzed. Results: All 18 patients had findings of maxillary sinus floor perforation or penetration by dental implants on CT. Fifteen of the 18 patients underwent ESS. Two patients had the dental implants removed before ESS and did not experience recurrence. Four patients had recurrence and the dental implants were removed before revised ESS. They did not experience recurrence again after the revised operation. The other nine patients had their dental implants preserved and did not experience recurrence during follow-up. None of the 15 patients required a Caldwell-Luc operation. Conclusion: In patients with DIrCRS, ESS can be used as the first surgical choice with good prognosis and low morbidity. Although most cases of DIrCRS are caused by dental implants penetrating into the maxillary sinus, the dental implants can be preserved unless there is severe periimplantitis or recurrence of sinusitis. Nonetheless, the sinus mucosa above the dental implants must be kept intact during ESS.